(untitled) (Plant Tissue Culture and Biotechnology, 2018)
Tissue culture and genetic transformation in maize are very laborious. The existing regeneration methods, which mainly use immature embryos as starting material, are highly genotype-dependent. Leaf segments can be used as an alternative explant source to produce embryogenic calli. Although a reliable leafbased regeneration and transformation system has been recently reported for maize, however, the genotype-dependency of this method has not been described yet. To this end, we evaluated the production of embryogenic calli from young leaves of several maize genotypes. The results showed that, overall callus induction potential as well as embryogenic callus induction rate is significantly different among the tested genotypes, demonstrating the genotypedependency of this system. However, induced embryogenic calli from different genotypes remained their embryogenic capability during several callus multiplication rounds. In addition, embryogenic calli showed high potential for biolistic-based genetic transformation, as revealed by transient GUS expression. Plant Tissue Cult. & Biotech. 28(2): 261-268, 2018 (December)